Innovative social approaches to enhance the ecological sustainability of Kopi Luwak Village in Prangat Baru, East Borneo - Muhammad Busyairi; Abdul Kahar; Dharma Saputra; Asih Soenarih; Vivi Apriliyani; Dita Aprilia; Azis Rahmat Pratama; Marista Sihombing; Aulia Miftahul Jannah (Universitas Muhammadiyah Magelang, 2024)
Nestled in the hilly region of Marangkayu District, Prangat Baru Village experiences an annual rainfall of 194.5 mm and sits at an elevation of 150 meters above sea level. The Kopi Luwak Village Ecology Strengthening Program in Prangat Baru is an expansion of a previous initiative. Its primary objective is to enhance the economic standing of the village’s coffee farmers through a three-pronged approach, aiming for program self-sufficiency by 2024. These pillars include cultivating Liberica coffee, conserving the Asian palm civet, and promoting Kopi Luwak Village as an educational tourism destination. The program employs a strategy of socialization, training, and mentorship for the local coffee farmers. Implementation results have demonstrated a significant improvement in the economic well-being of the participating farmers and their community. Moreover, the program’s successful practices have inspired other farmer groups to replicate the initiative.